2018
DOI: 10.1007/s10943-018-0623-1
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Church and Trait: Trait Death Anxiety is Universal, Distressing, and Unbuffered by Worldview in Emerging Adults

Abstract: We begin with a review of death anxiety in emerging adults and then report on a descriptive survey study using the Revised Livingston-Zimet Death Anxiety Scale (RLZDAS). Research questions dealt with the RLZDAS' factor structure, demographic patterns, and hypothesized correlations with distress and religiosity/spirituality. We surveyed university-enrolled emerging adults (n = 706). Findings included a 3-factor solution on the RLZDAS (cognitive, repressive, and affective) and no appreciable relationships with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Since COVID-19 vaccination intention and religiosity are likely to be influenced by key demographics (e.g., age, household income), we collected key demographic variables for statistical control (Amit Aharon et al 2018 ; Pashak et al 2020 ). More specifically, participants reported on the following important demographic characteristics: age (continuous variable), sex (female, male) race (White, African American, Asian, Hispanic, American Indian, Middle East and North Africa (MENA) and others), and marital status.…”
Section: Methodsmentioning
confidence: 99%
“…Since COVID-19 vaccination intention and religiosity are likely to be influenced by key demographics (e.g., age, household income), we collected key demographic variables for statistical control (Amit Aharon et al 2018 ; Pashak et al 2020 ). More specifically, participants reported on the following important demographic characteristics: age (continuous variable), sex (female, male) race (White, African American, Asian, Hispanic, American Indian, Middle East and North Africa (MENA) and others), and marital status.…”
Section: Methodsmentioning
confidence: 99%
“…Although individuals may have different religious beliefs across different sociocultural contexts, the understanding of the inevitability of death appears to be universal, so is the anxious feeling toward death (Lehto & Stein, 2009). Studies have reported that people showed similar levels of death anxiety despite differences in religious beliefs (Pashak et al, 2020) and across different religious affiliations (i.e., Christianity vs. Buddhism in Thailand) (Chaiwutikornwanich, 2015).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Death anxiety should be addressed directly by emerging adults, for whom the phenomenon underlies various forms of distress and diagnosable psychopathology and is universal irrespective of one's worldview, belief system, or demographics (Pashak et al, 2018). "The possibility of death jars [one] loose from the treadmill of time" (May, 1953, p. 271) insofar as it provides a vivid and life-affirming reminder of one's impermanence.…”
Section: Promoting Existential Learning Via Confronting Death Anxietymentioning
confidence: 99%